ULTRAFAST TRANSMISSION ELECTRON MICROSCOPY - A. A. Ischenko; Yu. I. Tarasov; E. A. Ryabov; S. A. Aseyev; L. Schäfer (Тонкие химические технологии)
Ultrafast laser spectral and electron diffraction methods complement each other and open up new possibilities in chemistry and physics to light up atomic and molecular motions involved in the primary processes governing structural transitions. Since the 1980s, scientific laboratories in the world have begun to develop a new field of research aimed at this goal. “Atomic-molecular movies” will allow visualizing coherent dynamics of nuclei in molecules and fast processes in chemical reactions in real time. Modern femtosecond and picosecond laser sources have made it possible to significantly change the traditional approaches using continuous electron beams, to create ultrabright pulsed photoelectron sources, to catch ultrafast processes in the matter initiated by ultrashort laser pulses and to achieve high spatio-temporal resolution in research. There are several research laboratories all over the world experimenting or planning to experiment with ultrafast electron diffraction and possessing electron microscopes adapted to operate with ultrashort electron beams. It should be emphasized that creating a new-generation electron microscope is of crucial importance, because successful realization of this project demonstrates the potential of leading national research centers and their ability to work at the forefront of modern science.